Bosnia and Herzegovina : 2008 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Bosnia and Herzegovina. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This Article 2008 IV Consultation highlights that Bosnia and Herzegovina's economy has been exhibiting robust growth, but imbalances have emerged. The current account deficit has widened and underlying inflation has picked up. Procyclical fiscal policy has added to these imbalances. Moreover, large public-sector wage increases threaten to spill over to private sector settlements, thus exacerbating inflation pressures and weighing on competitiveness. Credit growth has started to slow down, and tightened financial conditions have resulted in a fall in bank profitability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet